2022
DOI: 10.3389/fphy.2022.1045196
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the spatial scales of mass and heat transfer in direct plasma sources for activating liquids

Abstract: When plasma is in direct contact with liquid, an exchange of mass and heat between the two media occurs, manifested in multiple physical processes such as vaporization and multiphase heat transfer. These phenomena significantly influence the conditions at the plasma–liquid interface and interfere with other processes such as the multiphase transport of reactive species across the interface. In this work, an experimentally validated computational model was developed and used to quantify mass and energy exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…16,49 Silsby et al reported that upon plasma-liquid interaction, a high-temperature thin liquid film is formed in the plasma-liquid interface region. 50 The electric field and the localized heat generated due to the transfer of highly energetic reactive species increase the temperature of the overall system. 51 In this high-temperature liquid region, the Mo species undergoes a chemical reaction with plasma-generated reactive oxygen species (Step: 9).…”
Section: Papermentioning
confidence: 99%
“…16,49 Silsby et al reported that upon plasma-liquid interaction, a high-temperature thin liquid film is formed in the plasma-liquid interface region. 50 The electric field and the localized heat generated due to the transfer of highly energetic reactive species increase the temperature of the overall system. 51 In this high-temperature liquid region, the Mo species undergoes a chemical reaction with plasma-generated reactive oxygen species (Step: 9).…”
Section: Papermentioning
confidence: 99%
“…As described above, the sodium loss mechanism is likely due to oxygen recombination, which is favored at low gas temperatures. Therefore, a likely explanation is that as the gas flow rate increases, the temperature in the discharge decreases [2,20] resulting in an increase in the recombination rate of sodium. Furthermore, fluid flow simulations [20] have shown that the gas temperature gradient near the liquid surface reduces by a factor of 2 when the helium flow rate is doubled.…”
Section: Nomentioning
confidence: 99%
“…As mentioned in the introduction, a few mechanisms like Taylor cone formation (electrospray) [8], evaporation/ion bombardment [2,9] and Chemical Vapor Generation [13] have been hypothesized as potential mechanisms for the solute transfer from the liquid to the gas phase.…”
Section: Potential Role Of Chemical Vapor Generationmentioning
confidence: 99%
See 1 more Smart Citation